2007
DOI: 10.1177/1362361307070908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing in children with autism by using TEOAE and ABR

Abstract: The aim of the newborn hearing screening programme is early detection of hearing loss. Transient evoked otoacoustic emissions (TEOAE) and automised auditory brainstem response (A-ABR) are effective, objective and valuable test batteries for newborn hearing screening, and they should be used together. The purpose of this study is to determine which test battery is more accurate and can be used as the gold standard. A total of 933 newborn children were included in this study, of which 602 were girls and 331 boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 15 publications
8
60
1
3
Order By: Relevance
“…These studies confirm the existence of a greater ASD risk in hearing-impaired subjects [7,8,32,39,40], suggesting that the social interaction difficulties suffered by these people are even worse because of sensory deprivation [8]. This situation underlines the need to identify cases earlier because these subjects require different and additional care [40].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These studies confirm the existence of a greater ASD risk in hearing-impaired subjects [7,8,32,39,40], suggesting that the social interaction difficulties suffered by these people are even worse because of sensory deprivation [8]. This situation underlines the need to identify cases earlier because these subjects require different and additional care [40].…”
Section: Discussionsupporting
confidence: 60%
“…Surprisingly, there is no data in the literature regarding the investigation of suspected ASD among subjects undergoing hearing evaluation, although this type of evaluation is cited in studies conducted with ASD subjects [22,24,25,26,37,38,39]. …”
Section: Discussionmentioning
confidence: 99%
“…While there have been many studies using the ABR to characterize hearing and auditory function in individuals with AD, fi ndings have been mixed to date. Several investigators have reported prolongations in clickevoked ABR wave latencies and/or interpeak intervals (IPI) in children and adults with AD (Tanguay et al, 1982;Gillberg et al, 1983;Wong & Wong, 1991;Maziade et al, 2000;Tas et al, 2007;Kwon et al, 2007), however others report no group differences (Rumsey et al, 1984;Courchesne et al, 1985;Tharpe et al, 2006).…”
Section: Sharon Fujikawa-brooksmentioning
confidence: 97%
“…The DPOAE levels and SNRs at several frequencies in addition to the overall values for the TEOAE levels were higher in the autism group compared with those in the control group. Studies of the auditory characteristics of children with autism showed that the OAE responses in children with autism were either equivalent to those in typically developing children [6,12] or lower [20,21] . In a study on children with normal hearing, the TEOAE SNRs and DPOAE levels were similar in children with autism and typically developing control subjects [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, OAEs are simple to measure, and the measurements do not greatly depend on the cooperation of the patient. According to the literature, such objective methods provide a practical way of detecting auditory problems in non-cooperative children [4,20] . Studies on the OAEs of children with and without autism revealed different results, with some showing no differences between groups and others showing a difference in the emission responses of children with autism [6,12,21] .…”
Section: Introductionmentioning
confidence: 99%